Gamma knife radiosurgery in non small cell lung cancer patients with brain metastases: treatment results and prognostic factors - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2010)
Purpose: To evaluate the efficacy of gamma knife radiosurgery (GKRS) for the treatment of brain metastases from non small cell lung cancer (NSCLC) and find out the prognostic factors for overall survival. Methods: Between February 1997 and August 2003 100 patients underwent treatment for 184 brain metastases from NSCLC, either for recurrence (n=49) or with a new diagnosis (n=51). Median age was 55 years and 77 patients were male. Seventy-eight of the patients received whole brain radiotherapy (WBRT)prior to or after GKRS and 26 patients had surgical removal of the metastasis. Imaging and clinical status were monitored every 3 months following treatment. Kaplan-Meier survival curves, Cox proportional hazards regression for risk factor analysis were used. Results: The median follow up after the procedure was 8 months and after the diagnosis 11 months. The median overall survival for all patients was 9 months from the date of GKRS and 14 months from the diagnosis of brain metastasis. Local tumor control was achieved in 95% of the lesions. In multivariate analysis, adenocarcinoma histology, Karnofsky performance status (KPS) score >= 80, 1-3 metastases and tumor diameter <2 cm were related to longer survival. Addition of WBRT did not have any effect on overall survival. Conclusion: Gamma knife surgery appears to be effective in treating patients with brain metastases from NSCLC, either alone or with WBRT in selected groups of patients.
Keywords: lung cancer; metastases; prognostic factors; radiosurgery; LOCAL TUMOR-CONTROL; LONG-TERM OUTCOMES; STEREOTACTIC RADIOSURGERY; RADIATION-THERAPY; TREATMENT OPTIONS; RANDOMIZED-TRIAL; RADIOTHERAPY; MANAGEMENT; CARCINOMA; SURVIVAL